A1.13 The prevalence of a raised interferon gene signature is increased in early ra and is associated with worse disease activity. (24th February 2016) - Cooles, FAH; Anderson, AE; Hilkens, CMU; Isaacs, JD
Abstract : Background and Objectives: An interferon gene signature (IGS) is present in 20–30% of established rheumatoid arthritis (RA) patients where it does not correlate with disease activity. However immunomodulatory treatment may mask underlying associations so we investigated both the prevalence of the IGS and associations with disease activity in early RA. Materials and Methods: For steroid naïve patients with a new ACR/EULAR RA diagnosis we recorded: swollen joint count (SJC), tender joint count (TJC), patient visual analogue scale, DAS-28, CRP, ESR, rheumatoid factor, anti-CCP antibody, serum IL-6, IL-8, TNF-α, IFN-γ (MSD) and whole blood (Tempus, Life Technologies) RT-PCR expression of 5 interferon-α response genes, IRGs (MXA, IFI6, OAS-1, ISG-15, IFI-44L). Some patients had IRG expression repeated at 3 months. In addition established RA, SLE patients and healthy controls had the above IRGs quantified. Patients were defined as "high IGS" if the sum of their IRGs was ≥ 2 standard deviations above healthy control mean sum IRG expression. Statistics performed: linear regression/Mann Whitney-U (Graphpad Prism). Significance when p < 0.05. Results: Cohorts included 50 early RA (Male:Female 1:2, median age 57 [30–91]), 18 healthy controls (Male:Female 1:1, median age 22 [25–57]), 15 established RA (Male:Female 1:7, median age 73 [52–78]) and 24 SLE (Male:Female 1:10, median age 53 [33–69]). There was no significant association between age/sex and IRGs. In early RA 47% had a high IGS compared with 33% established RA. Total IRG expression was significantly upregulated in early RA compared with established RA and comparable to SLE. Furthermore after 3 months of treatment in early RA (n = 9) there was a significant fall in MxA, ISG15, IFI6 and IFI44L. At diagnosis MxA and OAS1 demonstrated significant associations with DAS-28, TJC and CRP. MxA also significantly associated with ESR and serum IL-6 and OAS1 with SJC. There were no other significant associations for remaining clinical parameters, cytokines or autoantibodies. Conclusions: We report an increase in IRG expression in early RA which associates with increased disease activity and falls with time/treatment. Other autoimmune conditions, such as primary Sjogrens, suggest type 1 interferons are important in disease initiation, and we propose IFN-a may play a role in early RA pathophysiology. Further work is needed to determine its relative importance.